IMPLEMENTASI SURAT EDARAN MAHKAMAH AGUNG NOMOR 3 TAHUN 2015 PADA PENGADILAN AGAMA SAWAHLUNTO - Muhammad Farhan; Eficandra Eficandra; Roni Efendi (Institut Agama Islam Negeri Batusangkar, 2020)
The urgency of this research is to examine the implementation of the Supreme of the Court Circular Number 3 2015 on the addition of livelihoods for children from 10% to 20% per year. Since the determination Supreme of the Court Circular in the Family Court of Sawahlunto, in 2018 were 7 decisions have been made, 3 to applicated and 4 doesn’t. The inequality when considering the jury leads to three fundamental questions: What is the position of Supreme of the Court Circular in the concept of the positivist legal philosophy? What are the Judges considerations to implementing and not implementing Supreme of the Court Circular? Howabout the Islamic Law perspective to Supreme of the Court Circular in terms of adding child livelihood? To answer the object of research, the implementation Supreme of the Court Circular Family Court Sawahlunto is extensively examined as sociological/ empirical legal research. The results of this research philosophically Supreme of the Court Circular is a harmonization between Islamic law and positive law, on the condition that Supreme of the Court Circular offers the jury a guarantee of legal certainty when deciding on the addition of a child. Consideration of the jury in the implementation of Supreme of the Court Circular to ensure that children's livelihoods are met in terms of economic needs that further improve and maintain descendant relationships for those who do not implement Supreme of the Court Circular due to the limited ability of their fathers. Supreme of the Court Circular’s perspective on Islamic law regarding the addition of a child at 10% to 20% per year is relevant to the problem of the Maslahah Mursalah, which is to maintain hereditary relationships.